(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article seeks to analyze the socio-cultural existence of the cult of ancestors in the worldview of the Kazakhs in a historical context and to show modern trends in the implementation of the ancient beliefs. The study of the reception of the Kazakh heritage in the field of contemporary culture remains one of the urgent scientific problems. The solution to the goal is carried out through the analysis of rites, rituals, customs, and traditions that make up the spiritual foundation of the Kazakh people, and is embodied in the cult of ancestors.The veneration of the deceased ancestors of the Kazakhs is an important part of spiritual life. Since ancient times, the ancestors of the Kazakhs sincerely believed that the spirits of deceased ancestors are constantly watching living relatives patronize them in real life. People believed that the spirits of the ancestors continue to be interested in the lives of their descendants, and by intervening in real people’s lives, support. The authors noted the ambiguous attitude of Islam have remained to this day the cult of ancestors in the Kazakh traditional culture. Modern imams reject the worship of ancestors, calling it a manifestation of pagan beliefs, the attribution of partners to God, which is unacceptable for the Islamic faith. A big role of honoring the spirits of famous people whose names are pronounced in difficult situations is highlighed. In their honor, there were brought animal sacrifices, went to worship to their graves. The tombs were regarded as symbols and recognition of the greatness of their ancestors, testifying to the invisible sacred connection with the world of the dead. The monument was a meeting place between people and the spirit of the ancestor and bridge special ritual contact with the other world of spirits, living in a different dimension, a different space. Different kinds of sacrifying to the spirits were considered, which according to the authors, were the desire to be with them in the balance in the relationship; the veneration of the saints; belief in afterlife; sacrifice; the knowledge of his ancestry. In the study, it was noted that many of the ceremonies connected with the cult of ancestors-spirits, practiced in our days, which indicates inherent in the modern Kazakhs of the elements of the tengrian worldview. This article used a large number of factual examples proving how the worship of ancestors is holy honored by Kazakh people. This analysis, according to the authors, contributes to deeper penetration and understanding of the ritual procession of the ancient beliefs of the Kazakh people. Key words: arwah, balbal, spirits of ancestors, tengriism, «as» (meal).